HIV/AIDS em usuários de crack institucionalizados em Goiânia, Goiás: perfil epidemiológico e subtipos virais - França, Divânia Dias da Silva (2016)
Infection by human immunodeficiency virus (HIV) is a serious global public health problem. An estimated 78 million people have been infected. The burden of this infection is concentrated in high vulnerability groups, such as drug users. The objective of this study was to analyze the serological, epidemiological, and molecular profile of HIV infection in institutionalized crack users in Goiania, a large city in Central Brazil. This is an observational, analytical, cross-sectional study conducted among crack users in treatment in a mental health referral facilityin Midwestern Brazil. From August 2012 to April 2013, 600 crack users were recruited. All were interviewed and tested for HIV by enzyme-linked immunosorbent assay (ELISA). The samples that tested positive for anti-HIV1 were subjected to detection of HIV RNA by RT-PCR and genotyped by sequencing. Of the total enrolled participants: about half came from outside the city (50.3%), were predominantly male (84.5%), young (median: 30 years), had low education (8.4 years of school), were self-declared mixed race (61.5%), single (66.5%) and religious (74.3%). Nearly three-quarters were not formally employed, and 20.3% reported a history of life on the street in the last 180 days. Of the total, 2.8% (95% CI: 1.7 – 4.4%) were anti-HIV1 positive, ranging from 2.2% (95% CI 1.2 – 3.9) in men and 6.5% (95% CI 3.2 – 14.2) in women (p = 0.04). Logistic regression analysis revealed that history of sexual intercourse with a carrier of HIV (adjusted OR: 12.60; p = 0.001) and history of life on the street (adjusted OR: 4.43; p = 0.025) were predictors of HIV- 1. The variables: history of sexually transmitted infections (adjusted OR: 3.24; p = 0.057), not using a condom (adjusted OR: 2.84; p = 0.088) and consumption of more than 10 rocks/portions of crack daily (adjusted OR: 2.81; p = 0.085) were marginally associated with HIV infection. In 12 of 17 HIV-1 samples, subtype identification was possible with subtype B being detected in eight samples (66.7%), F1 and C in one sampleeach (8.3%), and recombinant BF in two samples (16.7%). These results highlight the need for effective strategies to prevent HIV infection in crack users, with an emphasis on health education, implementation of harm reduction measures and control of sexually transmitted diseases.